Electrocatalytic Study of Carbon Dioxide Reduction By Co(TPP)Cl Complex - Khalaf Alenezi (Journal of Chemistry)
Carbon dioxide (CO2) is notorious for being a greenhouse gas and is the most important cause of global warming. However, it can be converted into useful products as it is a source of carbon. Reduction of CO2 is therefore an attractive research topic for many chemists. Different methods of electrocatalytic reduction of CO2 have been reported previously. Since CO2 is very stable, the direct electroreduction of CO2 into CO requires high potential at −2.2 V versus Ag/AgCl. In this work, CO2 reduction was carried out by the photoelectrocatalysis of CO2 in the presence of cobalt(III)tetraphenylporphyrin [Co(TPP)Cl] at −1.85 V with a current efficiency of 71%. At illuminated p-type silicon photocathode, the reduction of CO2 into CO was performed at a potential of 300 mV which is positive. However, at the same conditions, potential of −1.55 V with a current efficiency of ca 65% is required for the carbon electrode.